2023
DOI: 10.55908/sdgs.v11i4.892
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management Practice and Organizational Performance: The Mediating Role of Business Model Innovation

Bojuwon Mustapha,
Banji Rildwan Olaleye,
Oyewole Bernice Yetunde
et al.

Abstract: Purpose: This paper examines the effect of risk management practices on organizational performance and the mediating role of business model innovation in Nigeria.   Design/Methodology/Approach: This research uses quantitative research methods. The paper uses a sample of 83 employees, with data collected through an online questionnaire using a Likert scale using a scale of 5, and the data was analyzed using partial least square structural equation modeling (PLS-SEM). The stages of data analysis begi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 78 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…The convergence validity of the measurement model was confirmed by Cronbach's alpha, composite reliability, and rho_A values that were all greater than 0.5; likewise, the AVEs are over the threshold of 0.5 (Dijkstra & Henseler, 2015;Fornell & Larcker, 1981). The reduced AVE value of changed scales provides support for their "convergent validity" (Anifowose et al, 2022;Iyer, 2017;Mustapha et al, 2023;. Therefore, the aggregate metric shows a satisfactory match and substantial predictive potential.…”
Section: Summary Of Measurement Results For the Model; Contains "Part...mentioning
confidence: 70%
“…The convergence validity of the measurement model was confirmed by Cronbach's alpha, composite reliability, and rho_A values that were all greater than 0.5; likewise, the AVEs are over the threshold of 0.5 (Dijkstra & Henseler, 2015;Fornell & Larcker, 1981). The reduced AVE value of changed scales provides support for their "convergent validity" (Anifowose et al, 2022;Iyer, 2017;Mustapha et al, 2023;. Therefore, the aggregate metric shows a satisfactory match and substantial predictive potential.…”
Section: Summary Of Measurement Results For the Model; Contains "Part...mentioning
confidence: 70%
“…The veracity of this claim is strengthened by the fact that these business owners learn by real-world business experience, a procedure frequently connected to experiential learning. The study on business expirience can be observed in Mustapha's study (Mustapha et. al.. 2023).…”
Section: Business Experiencementioning
confidence: 99%
“…Industry character strongly influences the inventory and purchasing performance relationship (Basu & Wang, 2011);Hofer et al, 2012); (Priniotakis & Argyropoulos, 2018). practices for risk management and financial performance had a direct and huge effect on financial performance (Mustapha et al, 2023). Using a clustering technique to cluster data with the same characteristics helps researchers decrease group variation (Sharma et al, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%